Dampak Penanaman Modal dalam Negeri, Bi Rate, dan Nilai Tukar (Kurs) terhadap Indeks Harga Saham Gabungan di Indonesia - Mohammad Naufal Bashor Alfi; Niniek Imaningsih (Syntax Corporation Indonesia, 2024)
This study aims to analyze the impact of the Domestic Investment program (PMDN), Bank Indonesia interest rate (BI Rate), and exchange rate on the Jakarta Composite Index (JCI) in Indonesia. To test the relationship between the independent variable (PMDN, BI Rate, and exchange rate) and the dependent variable (JCI) over a certain period of time, multiple regression analysis method is used. This research uses data obtained from various reliable and relevant sources. The findings of this study are expected to provide a deeper understanding of the factors that influence JCI in Indonesia and provide insight for policymakers to improve the investment climate. The conclusions and policy recommendations generated from this study are expected to be able to make a positive contribution to Indonesia's economic development in the long term.